The impact of new terminals on telecommunications carriers and TV media companies - Shinichiro Terada (International Telecommunications Society (ITS), 2011)
This paper investigates the impact of new terminals emergence, such as smartphones, tablet personal computers and smart TVs, on telecommunications carriers and TV media companies. We choose event study methodology to analyze this research. Our research question is Does the emergence of new terminals generate significant imact on the telecommunications carriers and the TV media companies? The results show that the impacts of new terminals appear differently on telecommunications carriers and on TV media companies. 1) Regarding telecommunications carriers, some of the smartphone and tablet PCs generate significant positive imapct or no impact on smartphoner (or tablet PC)-affiliated telecom carriers, but generate significant negative impact on non-smartphone (or tablet PC)-related telecom carriers, 2) Regarding TV media companies, tablet PCs and smart TVs do not generate any significant impact on any researched TV medeia companies. The results imply some further reasons why the new terminals emergences generate no significant imapct on TV media companies. The paper presents three possible reasons. 1) The new terminals are not so powerful that they do not influence TV media companies. 2) The new terminals are sufficiently powerful but their imapct does not go to the TV industry. 3) The new terminals are sufficiently powerful but the services by the new terminals do not compete against incumbent TV media services.
Keywords: L10; 330; smartphone; tablet PC; smart TV; telecommunications carrier; TV media company; event study